2011
DOI: 10.1007/s10162-011-0257-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Behavioral and Physiological Spectral-Ripple Discrimination

Abstract: Previous studies have found a significant correlation between spectral-ripple discrimination and speech and music perception in cochlear implant (CI) users. This relationship could be of use to clinicians and scientists who are interested in using spectral-ripple stimuli in the assessment and habilitation of CI users. However, previous psychoacoustic tasks used to assess spectral discrimination are not suitable for all populations, and it would be beneficial to develop methods that could be used to test all ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 50 publications
7
79
0
Order By: Relevance
“…In principle, the available cues are larger at greater modulation depths. Our previous reports used a spectral ripple modulation depth of 30 dB (Won et al, 2007(Won et al, , 2011, whereas Experiment 1 in the present study used a spectral modulation depth of 13 dB. This experiment compared spectral-ripple discrimination thresholds obtained with spectral modulation depths of 13 and 30 dB.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In principle, the available cues are larger at greater modulation depths. Our previous reports used a spectral ripple modulation depth of 30 dB (Won et al, 2007(Won et al, , 2011, whereas Experiment 1 in the present study used a spectral modulation depth of 13 dB. This experiment compared spectral-ripple discrimination thresholds obtained with spectral modulation depths of 13 and 30 dB.…”
Section: Introductionmentioning
confidence: 82%
“…Spectral-ripple discrimination, originally developed to investigate the spectral resolution of the normal auditory system (e.g., Supin et al, 1994Supin et al, , 1998Supin et al, , 1999, has recently gained a wide range of attention in the cochlear implant (CI) research field (e.g., Henry and Turner, 2003;Henry et al, 2005;Won et al, 2007;Litvak et al, 2007;Saoji et al, 2009;Drennan et al, 2010;Won et al, 2010Won et al, , 2011Anderson et al, 2011). These previous studies demonstrated that spectral-ripple discrimination correlates with vowel and consonant recognition in quiet (Henry et al, 2003(Henry et al, , 2005Saoji et al, 2009), speech perception in noise (Won et al, 2007), and music perception .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the FFR recordings, 100 unique versions of the narrowband noise were generated and randomly ordered. Presenting multiple versions of the noise reduces the likelihood that envelope-following responses would be elicited because the envelope would be different for each noise version (e.g., Won et al 2011). A single stimulus onset polarity was used, which emphasizes phase-locked responses to the fine structure of the 500 Hz carrier frequency (for a review, see Aiken and Picton 2008).…”
Section: Physiological Recordingsmentioning
confidence: 99%
“…Spectral ripple task can predict spectral resolution ability 8 . Short term memory and other cognitive abilities are the most essential factors for the discrimination of the stimulus 13 . There is enhanced memory in visually impaired individuals as compared to sighted participants 14 .…”
Section: Discussionmentioning
confidence: 99%